Determination and selection of indicators in a grassland based on a multiple mixture of creeping legumes with fattening cattle - Lok, Sandra; Crespo, Gustavo; Torres, Verena; Ruiz, Tom?s E.; Fraga, S.; Noda, Aida (Cuban Journal of Agricultural Science, 2011)
In a grassland based on a mixture of creeping legumes (Pueraria phaseoloides, Macroptilium atropurpureum and Neonotonia wightii) for the fattening of growing cattle, the performance of soil and pasture indicators was determined during three consecutive years and those that reflected the best their stability were selected. Through the analysis of principal components, three groups of indicators were obtained: vegetation, physico-chemical and biological indicators of the soil. Those with preponderance value higher than ? 0.78 and that accounted for, at least, 65 % of the variance accumulated were chosen. In the vegetation, 37 indicators were studied and nine were selected, such as: the plant cover, the naked soil, the basic pasture density, the presence of natural pastures and the botanical composition. Out of the 71 soil indicators, eight of the physico-chemical were selected, in which the index of plasticity, the distribution of aggregates in humid and in dry conditions, the structural stability, the n value and the resistance to penetration showed the highest contribution to the system variability; whereas that, out of the biological indicators, eight were also selected in which the underground phytomass, the macrofauna and the mesofauna showed the best contribution. The grassland progressed in time by the increment of the population of the basic pasture (Neonotonia wightii) from 11.2 to 34.4 plants m-2 and by its stability in the biomass availability, which had no differences between years for each climatic season, with values of 2.69 and 3.76 t DM ha-1 for the dry and rainy seasons, respectively. Besides, there was improvement of the edaphic characteristics manifested in the distribution of aggregates lower than 1 mm of diameter in dry conditions and the index of plasticity, which decreased with the exploitation time of the system. In this study, there are tables with ranges of confidence values for the indicators proposed, that could serve as useful, trustworthy and sensible tools, to know the changes occurring in this type of grassland and that could be used in research, teaching and production. Key words: indicators, stability, legumes, grassland.